Bilateral agreement for academic years 2010/2013 Socrates programme: Higher Education - Erasmus between Universidade Lusíada de Lisboa and Universidad de Málaga - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme. - Subject area: Economics.